Literature: Structure, Sound, and Sense - Perrine, Laurence (New York Harcourt Brace Jovanovich, Publishers, 1983)
This book is intended for the student who is beginning a serious study of imaginative literature. It provides a comprehensive introduction to the principal forms of fiction, poetry, and drama.
Keywords: Literature